Under the oak tree : the novel. Volume 2 - Kim, Suji (Inklore, 2025)
"As her first winter in Anatol turns to spring, Lady Maximilian finds herself confronting an unfamiliar feeling: hope. Her voice and her magic strengthen every day; the only parts of Calypse Castle left to refurbish are its gardens, which she plans to fill with blooming flowers; and the way her husband, the recalcitrant war hero Sir Riftan, looks at her from across their bedroom makes her feel, for the first time in her life, that she might be worthy of love and affection.However, Maxi's life is never that easy. Just as she begins to feel at home with Riftan, Maxi receives a surprise visit from Princess Agnes, the renowned sorceress who might have become Riftan's wife if he'd decided to divorce Maxi after the Dragon Campaign. Not at all what Maxi expected, the princess stirs up complicated emotions and politics that could lead to monumental changes in Maxi and Riftan's relationship."--Provided by publisher.